Editorial - Calizaya Calizaya, Hugo (2019)
Editorial The effort of the intellectual development of a superior house of studies is reflected in the scientific and academic production of its population of students. It is our main desire to promote, through an increasingly visible diffusion, research that has a social focus linked to problems of our regional and national environment This edition gathers the research production carried out during the academic year 2018. Our scientific journal Veritas et Scientia is already present through the virtual open platform OJS (Open Journal System), thus reaching a wide spectrum of readers and reviewers who , with their invaluable contribution, allow us to improve our editions more and more. In this opportunity, the selected articles consider the production of doctoral and master's programs in the field of teaching, law, engineering and other spaces in which we develop our academic work, as well as international guests who requested to publish their articles. Always attentive to initiatives that enrich knowledge, the platform already opening, with greater emphasis, the reception of online articles worldwide, now additionally covered by the recognition of CONCYTEC to journals registered in Latindex, as a criterion for evaluation of researchers at the national level. Dr. Hugo Calizaya Calizaya Director – Editor Veritas et Scientia